The Effects of Socrative-Based Online Homework on Learning Outcomes in Vietnam: A Case Study - Tran, Thi Ngoc Anh; Nguyen Thanh, Phong (International Journal of Interactive Mobile Technologies (iJIM), 2023)
In the educational digital transformation, the effective use of technological platform has been proved to support formative assessment and improve student learning outcomes. This research focuses on Socrative – a student response system (SRS) that has been appreciated by many recent studies. The quasi-experimental design is used to evaluate the impact of completing Socrative-based Physics online homework on students’ learning outcomes. Data were collected from 305 grade 10 students at two high schools in central Vietnam. The results showed that 152 students have participated in the homework on Socrative (experimental group), with an average score of 7.73/10 in the final exam; while the score of 153 students who did not participate in the activity (control group) was 5.31/10. The results of the survey indicated that students have positive attitudes toward the use of Socrative as an online homework platform. In addition, the students recommended that Socrative should be applied frequently in many subjects and exams in order to enhance their learning outcomes.